Contact and fumigant toxicity of Pinus densiflora needle hydrodistillate constituents and related compounds and efficacy of spray formulations containing the oil to Dermatophagoides farinae. Issue 6 (29th October 2012) - Lee, Ju‐Hee; Kim, Jun‐Ran; Koh, Young Ryull; Ahn, Young‐Joon
Abstract Background The toxicity of red pine needle hydrodistillate (RPN‐HD), 19 RPN‐HD constituents and another 12 structurally related compounds and the control efficacy of four experimental spray formulations containing RPN‐HD (0.5. 1, 2 and 3% sprays) to adult Dermatophagoides farinae were evaluated. Results RPN‐HD (24 h LC50, 68.33 µg cm−2) was toxic to mites. Menthol was the most toxic compound (12.69 µg cm−2), and the toxicity of this compound and benzyl benzoate did not differ significantly. High toxicity was also produced by α‐terpineol, bornyl acetate, geranyl acetate, thymol, linalyl acetate, terpinyl acetate, citral, linalool and camphor (18.79–36.51 µg cm−2). These compounds were more toxic than either deet or dibutyl phthalate. In vapour‐phase mortality tests, these compounds were consistently more toxic in closed versus open containers, indicating that their mode of delivery was largely a result of vapour action. RPN‐HD 3% experimental spray provided 95% mortality against adult D. farinae, whereas permethrin (cis:trans, 25:75) 2.5 g L−1 spray treatment resulted in 0% mortality. Conclusion In the light of global efforts to reduce the level of highly toxic synthetic acaricides in indoor environments, RPN‐HD and the compounds described merit further study as potential biocides for the control of Dermatophagoides populations as fumigants with contact action. © 2012 Society of Chemical Industry